2014
DOI: 10.5152/ucd.2014.2701
|View full text |Cite
|
Sign up to set email alerts
|

Can horizontal diameter of colorectal tumor help predict prognosis?

Abstract: Can horizontal diameter of colorectal tumor help predict prognosis? INTRODUCTIONColorectal cancer (CRC) is the third most common cancer among men and women in developed countries (1, 2). The preferred management of non-metastatic colon cancer is removal of the tumor and surrounding lymph nodes. Post-surgical treatment is closely related to the tumor node metastasis (TNM) staging system (3, 4).Depth of tumor penetration (T), regional lymph node involvement (N), and distant metastasis (M) are major parameters pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…One possible explanation for these findings is that the average size of the tumor was quite large (about 5-6 cm) in our study and a tumor with large diameter (especially more than 4.5 cm) could increase the risk of nodal involvement. 13 Also, some T1 tumors in our institute were treated by endoscopic removal or transanal excision thus resulting in those with large tumor or high-risk for nodal metastasis underwent oncological resection with LN-bearing area. Moreover, 50% of our cases were rectal cancer which was more prone to have LN metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for these findings is that the average size of the tumor was quite large (about 5-6 cm) in our study and a tumor with large diameter (especially more than 4.5 cm) could increase the risk of nodal involvement. 13 Also, some T1 tumors in our institute were treated by endoscopic removal or transanal excision thus resulting in those with large tumor or high-risk for nodal metastasis underwent oncological resection with LN-bearing area. Moreover, 50% of our cases were rectal cancer which was more prone to have LN metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to tumor differentiation and degree of invasion. In a study of 439 colorectal cancer patients, Balta et al 17 demonstrated that horizontal tumor diameter was significantly associated with extent of invasion and could be used in predicting prognosis. Because the present study included only rectal cancer patients and the patient number was smaller, we were unable to show this relationship statistically.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was associated with the ability of the tumor to undergo metastases (UICC, 2010). Study by Balta et al (2014) and showed a significant association between tumor size and metastatic state. TGF-βRII mutations found in >80% MSI cases are thought to have an important role in metastatic conditions.…”
Section: Frequency Of Msi (Msh2 Msh6 and Combination Ofmentioning
confidence: 98%